2014
DOI: 10.1111/jocn.12562
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to nutritional care for the undernourished hospitalised elderly: perspectives of nurses

Abstract: Aims and objectivesTo identify what nurses experience as barriers to ensuring adequate nutritional care for the undernourished hospitalized elderly.BackgroundUndernutrition occurs frequently among the hospitalised elderly and can result in a variety of negative consequences if not treated. Nevertheless, undernutrition is often unrecognised and undertreated. Nurses have a great responsibility for nutritional care, as this is part of the patient's basic needs. Exploring nurses' experiences of preventing and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 30 publications
7
105
2
9
Order By: Relevance
“…Moreover, several of the respondents were not aware of the above-mentioned guidelines (37). The health care personnel in our survey mentioned time as being the key obstacle to achieving good routines for assessing nutrition.…”
Section: Knowledgementioning
confidence: 95%
“…Moreover, several of the respondents were not aware of the above-mentioned guidelines (37). The health care personnel in our survey mentioned time as being the key obstacle to achieving good routines for assessing nutrition.…”
Section: Knowledgementioning
confidence: 95%
“…Analysis of nursing experiences indicates that patients frequently ask them to provide dietary information. Studies show that nurses are in constant contact with patients and continuously communicate with them (O'Mahony et al, 2011) and often receiving dietary questions from patients, but nurses are often busy with other tasks, such as documentation and medication (Eide et al, 2015). Nurses accompany patients throughout their health care to prevent and treat disease, so their knowledge about diet and dietary fibre is key to successful diet therapy, which is an essential part of a patient's non-pharmacological treatment (Rodrigues-Fisher, Bourguignon, & Good, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Norwegian studies among healthcare professionals have reported that only half or less of the patients identified to be at nutritional risk receive nutritional treatment [16,17]. A barrier to adequate nutritional care for malnourished patients in hospitals is the absence of routines, as demonstrated in qualitative studies among nurses in Norway and Sweden [18,19]. Nurses report lack of tools to estimate the patient's needs and the content of energy and protein in the hospital menus [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses report lack of tools to estimate the patient's needs and the content of energy and protein in the hospital menus [10]. They also experience insufficient knowledge and skills to identify and treat malnourished patients [18,20].…”
Section: Introductionmentioning
confidence: 99%